Implementation of Public Budget Governance Through a Web-Based Information System in the Government of Palangka Raya City to Achieve Good Governance - Prasetiyo, Jepri; Heriamariaty, Heriamariaty; Nugroho, Ani (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
In the era of digitalization, transparency and accountability in public budget management are the main demands in realizing good governance. The Palangka Raya City Government seeks to improve the effectiveness and efficiency of budget governance by implementing a website-based information system. This system aims to facilitate access to financial information, increase public participation, and minimize the potential for budget abuse. This research uses an empirical juridical approach to evaluate the effectiveness of SIMTEPRA in improving transparency and accountability of budget management in Palangka Raya City. Data were collected through interviews, direct observation and literature review, and analyzed descriptively-qualitatively to link existing regulations with field findings and identify implementation constraints and opportunities. With this system, it is expected that public budget management can be more transparent, accountable, and responsive to community needs. However, the successful implementation of this information system is highly dependent on supporting regulations, the readiness of human resources, and adequate technological infrastructure. Therefore, further studies are needed to assess the extent to which this system has been effective in supporting the principles of good governance in Palangka Raya City. The results of this study have implications for strengthening budget digitization regulations, increasing human resource capacity, building IT infrastructure, and optimizing e-government to support transparency, accountability, and data-based policies